Common metrics to assess the efficiency of clinical research. - Rubio, Doris McGartland (Evaluation & the Health Professions, 2013)
The Clinical and Translational Science Award (CTSA) program was designed by the National Institutes of Health (NIH) to develop processes and infrastructure for clinical and translational research throughout the United States. The CTSA initiative now funds 61 institutions. In 2012, the National Center for Advancing Translational Sciences, which administers the CTSA Program, charged the Evaluation Key Function Committee of the CTSA Consortium to develop common metrics to assess the efficiency of clinical research processes and outcomes. At this writing, the committee has identified 15 metrics in six categories. It has also developed a standardized protocol to define, pilot test, refine, and implement the metrics. The ultimate goal is to learn critical lessons about how to evaluate the processes and outcomes of clinical research within the CTSAs and beyond. This article describes the work involved in developing and applying common metrics and benchmarks of evaluation.